Unique Derivative Affixes In Simalungun Language (Morphosyntax Study) - Akmal Akmal; Iin Almeina Loebis; Chitra Latiffani (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2022)
Unique derivative affixes were focused on the morphosyntax process. This study was an interdisciplinary subject in linguistics. The affixations had a function as a form of word class or meaning. The affixations in Indonesian consconsist3 types, namely prefixes, suffixes, and confixes. This study explained the processes of the unique derivative affixes in the Batak Simalungun Language. The research method used the meant that this discussed the processes of morphology and then it was made in the sentences so that the morphological process was early and more completely in the linguistics. This study used the descriptive qualitative method by using the library (documents in the corpus) to interview a few native speakers who live in Batak Simalungun areas to get the data morals. Batak Simalungun Language affixes were prefixes, confixes, and suffixes. There were three prefixes : pa- , si-, ma- (mar), three confixes: par- (pa-)….-on, ha- ... -on/an, masi- . .. –an, and the last is only one suffix; -on. The derivative affixes in Batak Simalungun which the native speaker always expressed in the daily conversation, were so nwereral processes so t the other speakers did not realize that the word had got the affixations. There are two unique derivative affixiations on the suffix –on which had the passive meaning which had the prefix and the repetition prefix which the two first letters are repeated such as sapuh be sasapu. The position of affixation was a suffix, but the meaning was a prefix in passive voice meaning.